2023
DOI: 10.34067/kid.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles and Patterns of Kidney Disease Progression in C3 Glomerulopathy

Abstract: on behalf of the Spanish Group for the Study of Glomerular Diseases (GLOSEN) Key Points c Kidney survival in C3 glomerulopathy is significantly higher in patients with a disease chronicity score ,4 and proteinuria ,3.5 g/d, regardless of baseline eGFR. c A faster eGFR decline in C3 glomerulopathy is associated with higher probability of kidney failure. c Patients with glomerulopathy with a progressive reduction in proteinuria over time did not reach kidney failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“… 38 The same group has reported that in patients with C3G, a faster rate of decline in eGFR is associated with a higher probability of kidney failure. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 38 The same group has reported that in patients with C3G, a faster rate of decline in eGFR is associated with a higher probability of kidney failure. 16 …”
Section: Discussionmentioning
confidence: 99%